A new artifact!! - In life of a dental radiograph: A rare radiographic finding! Or a rare finding on a radiograph!! - Vela D Desai; Nitin Agarwal (Wolters Kluwer Medknow Publications, 2018)
Radiograph play as an important adjunct, in addition to history and clinical evaluation for the diagnosis of pathologies in head and neck region. A good and ideal diagnostic radiograph is essential for this purpose. An ideal radiograph is one that provides a great deal of information, the image exhibits proper density and contrast, have sharp outlines, and are of the same shape and size as the object being radiographed. Dental radiographs are subjected to various phases (procedures) right from the manufacturing and packaging until it is been exposed and processed. The diagnostic quality of a dental radiograph may be affected during any of these procedures and even after that. The authors here have noticed an interesting fault which is seldom mentioned in the literature.